The Effect of Person-Job Fit on Employee Performance Through Job Satisfaction as an Intervening Variable - Trysantika, Salsabila; Frianto, Agus; Kristyanto, Anang; Fazlurrahman, Hujjatullah (Social Science Studies, 2023)
The purpose of this study was to examine and analyze the effect of person-job fit on employee performance through job satisfaction at PT. Adikara Jaya Sentosa,tbk. This research is a causal research that uses a quantitative approach, with a population consisting of 75 commercial division employees. Data analysis in this study used SEM-PLS with the help of SmartPLS3 software. This results of this study prove that person-job fit has a significant positive effect on employee performance, person-job fit has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, and job satisfaction mediates between person-job fit employee performance.